Tough and mildew-proof formaldehyde-free soybean protein adhesive as well as preparation method and application thereof
By using components such as defatted soybean powder and epoxy compounds to build a crosslinking network structure, the problem of insufficient water resistance and mildew resistance of soy protein adhesives is solved, and the effects of high bonding strength and good water resistance and mildew resistance are achieved.
Patent Information
- Application Number
- CN202510016561.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional formaldehyde-based adhesives may release formaldehyde and volatile organic compounds during use, causing harm to the ecological environment and human health. At the same time, the water resistance and mildew resistance of soy protein adhesives are insufficient, resulting in low bonding strength and prone to mold.
Degreased soybean powder is used as the main agent, combined with epoxy compounds as the crosslinking agent, and graft modification of chitosan and polyethyleneimine is used to construct a tight crosslinking network structure to improve the water resistance and mildew resistance of the adhesive.
It significantly improves the bonding strength and water resistance of soy protein adhesives, enhances mildew resistance, and is simple in production process, reduces costs, and meets the requirements of sustainable development.
Smart Images

Figure CN119823713A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomass adhesives, and in particular to a soybean protein adhesive and a preparation method and application thereof. Background Art
[0002] Traditional adhesives are byproducts of petroleum processing. Currently, formaldehyde-based adhesives account for the largest proportion in the wood flooring production industry, mainly urea-formaldehyde resin (UF), phenol-formaldehyde resin (PF) and melamine-urea-formaldehyde resin (MUF). Among them, urea-formaldehyde resin is popular because of its low curing temperature, abundant raw materials, low production cost and excellent gluing performance. This resin accounts for more than 90% of the wood adhesive market. However, adhesives such as urea-formaldehyde resin may release a large amount of formaldehyde and volatile organic compounds during use. Traditional formaldehyde-based adhesives cause serious harm to the ecological environment and human health. Long-term exposure to low doses of formaldehyde can cause chronic respiratory diseases, nasopharyngeal cancer, colon cancer, brain tumors, menstrual disorders, neonatal chromosomal abnormalities, leukemia, etc., and cause memory and intelligence decline in adolescents. Biomass materials are widely used in the production and manufacturing of wood adhesives due to their renewability and environmentally friendly properties, and are expected to become a substitute for traditional adhesives to overcome environmental defects. These new adhesives are mainly derived from renewable biological resources, including protein-based adhesives, tannin-based adhesives, starch-based adhesives, lignin-based adhesives, etc. Adhesives prepared with soy protein as raw material have become a popular biomass-based adhesive due to its wide source, easy modification, low cost, and green environmental protection. However, as a natural biomass material, soy protein has a complex quaternary protein structure and a large number of hydrophilic groups, so when used as an adhesive material, the water-resistant bonding strength is low. In addition, soy protein glue also has the disadvantages of high viscosity, which makes it difficult to apply glue and easy to mold. To solve these problems, researchers introduced cross-linking agents for cross-linking modification, so that soy protein forms a dense cross-linking network, which can effectively improve the water-resistant bonding strength of soy protein adhesives. However, after cross-linking modification, the cross-linking density in the adhesive system increases, and the activity between molecules is hindered, resulting in increased brittleness of the adhesive. In addition, soy protein adhesives contain nutrients such as protein and polysaccharides, which are easily damaged by microorganisms and moldy. Therefore, it is particularly necessary to develop a soybean protein adhesive with high water resistance, good bonding toughness, and mildew and corrosion resistance.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a soy protein adhesive, which can effectively improve the problems of low bonding strength, poor water resistance and poor mildew resistance of conventional biomass adhesives; another object of the present invention is to provide a preparation method and application of the soy protein adhesive.
[0005] Specifically, the present invention provides the following technical solutions:
[0006] The invention provides a tough and mildew-proof formaldehyde-free soybean protein adhesive, comprising the following components in parts by weight: 100 parts of a main agent, 2-4 parts of a cross-linking agent, and 2-8 parts of a modifier, wherein the main agent is a defatted soybean powder solution, the cross-linking agent is one of bisphenol A epoxy resin, epoxy glycidyl ether, and triglycidyl amine, and the modifier is chitosan@polyethyleneimine.
[0007] Defatted soybean meal solution is a by-product of crushing defatted soybean meal.
[0008] The present invention unexpectedly found that the modified soybean protein adhesive prepared by using defatted soybean powder as the main agent, epoxy compound as the cross-linking agent, and polyethyleneimine modified chitosan synthetic modifier successfully improved the performance of soybean protein adhesive by constructing a tight cross-linked network structure. The soybean protein-based adhesive has high bonding strength, good water resistance, good mildew resistance, simple production process, and greatly reduced production cost. Among them, chitosan and polyethyleneimine are grafted and modified to destroy the living environment of bacteria, and the epoxy compound and chitosan@polyethyleneimine are combined to form a stable network cross-linked structure in the adhesive, which greatly improves its water resistance and mildew resistance.
[0009] The epoxy compound is selected as triglycidylamine. The combination of triglycidylamine and chitosan@polyethyleneimine synergistically forms a further stable network cross-linking structure in the adhesive, greatly improving its water resistance and mildew resistance.
[0010] Preferably, the epoxy glycidyl ether is selected from 1,2,3-propylene glycol triglycidyl ether.
[0011] In order to further improve the bonding strength and water resistance of the soy protein-based adhesive and reduce its brittleness, the present invention optimizes each component as follows:
[0012] Preferably, the concentration of the defatted soy flour solution is 20-30%.
[0013] Preferably, the preparation method of chitosan@polyethyleneimine comprises: adding 80-100 parts of 2-10% concentration glacial acetic acid to 2-10 parts of chitosan and dissolving them, adding 2-5 parts of polyethyleneimine, mixing, heating and evaporating to remove 60%-80% of the water, to obtain CS@PEI modifier.
[0014] Preferably, the preparation method of chitosan@polyethyleneimine comprises: adding 80-100 parts of 4-6% concentration glacial acetic acid to 5-10 parts of chitosan to mix and dissolve, adding 2.5-5 parts of polyethyleneimine to mix, heating and evaporating to remove 75% of the water to obtain CS@PEI modifier.
[0015] Preferably, the weight proportion of chitosan@polyethyleneimine is 4-6 parts.
[0016] Preferably, the preparation method of triglycidylamine comprises: adding epichlorohydrin and ammonia water in a mass ratio of 5:1 into a reaction kettle and stirring, reacting under the action of a catalyst at 20-25°C for 45-50h, and then at 30-40°C for 2-4h, wherein the catalyst is 0.5wt% of ammonium tricarboxylate;
[0017] The epichlorohydrin and ammonium hydroxide are removed by distillation to obtain a colorless slurry; an excess of sodium hydroxide solution is added to the colorless slurry, reacted at 18-22° C. for 1.5-3 hours, the sodium chloride precipitate is filtered, and a light yellow viscous liquid is obtained by vacuum distillation.
[0018] Furthermore, the concentration of the sodium hydroxide solution is 45-55%.
[0019] Preferably, the preparation method of triglycidylamine may also include the following steps:
[0020] (1) epichlorohydrin, ammonia water, diethylenetriamine and 1,2,4,5-pyromellitic acid are mixed in a molar ratio of 4-6:0.5-2:0.1-0.3:0.05-0.2, stirred evenly at 550-650 rpm, and ammonium trifluoride is added, and the mixture is reacted at 20-25° C. for 45-50 hours, and then at 30-40° C. for 2-4 hours;
[0021] (2) removing epichlorohydrin and ammonium hydroxide from the reaction product by vacuum distillation to obtain a colorless syrup with a branched structure; adding an excess of a 45-55% sodium hydroxide solution to the colorless syrup, and reacting at 18-22° C. for 1.5-3 hours; after the reaction is completed, filtering to remove sodium chloride, and subjecting the filtrate to vacuum distillation to obtain triglycidylamine.
[0022] Preferably, the defatted soy flour solution comprises defatted soy flour and a dispersion medium, and the dispersion medium is selected from one or more of tap water, softened water, and deionized water.
[0023] The present invention also provides a method for preparing the soybean protein adhesive, comprising the following steps:
[0024] According to any one of the above weight proportions, the defatted soybean powder solution is stirred evenly, and the crosslinking agent bisphenol A epoxy resin, epoxy glycidyl ether, one of triglycidyl amine and chitosan@polyethyleneimine are added in sequence and stirred evenly to obtain a soybean protein adhesive.
[0025] In the above technical scheme, a homogeneous soybean protein adhesive system is first prepared, and then the cross-linking agent triglycidylamine (TGA) is introduced to form a hard phase cross-linked network as a skeleton structure through the epoxy group and the active group on the soybean protein to undergo an epoxy ring-opening reaction. The rigidity and multi-branched structure brought by the benzene ring of the cross-linking agent itself are combined to effectively improve the cross-linking density and bonding strength of the adhesive; then, the cross-linking agent is introduced.
[0026] Preferably, in step (1), the stirring is performed at 500-1000 rpm for 10-15 min.
[0027] Preferably, in step (2), the stirring is carried out at 750-850 rpm for 15-20 min.
[0028] The present invention also provides application of the soybean protein adhesive in preparing plywood.
[0029] The beneficial effects of the present invention are:
[0030] (1) The present invention uses defatted soybean powder as the main agent, which solves the problem of formaldehyde pollution and harm to human health of traditional formaldehyde-based adhesives, reduces the consumption of petrochemical resources, and is conducive to promoting environmental sustainable development.
[0031] (2) Compared with the existing soybean protein adhesive, the water-resistant bonding performance of plywood prepared by the modified adhesive increased by 106.78% (1.22MPa), and the dry / wet tensile strain increased by 13.1% and 45.0%, respectively, significantly improving the bonding effect and meeting a wider range of application needs; the residual rate of the modified adhesive increased by 27.92%, the moisture absorption rate decreased by 12.26%, and the storage time increased from 2 days to more than 30 days. CS and PEI grafting modification destroyed the living environment of mold, and the cross-linking modification strategy formed a stable network cross-linking structure in the adhesive, greatly improving its water resistance and mildew resistance.
[0032] (3) The preparation process of the adhesive is relatively simple, the operation steps are clear, and it is easy to industrialize production, which reduces the training cost of operators and improves production efficiency; the natural materials (such as soybean protein and chitosan) used in the present invention have good biodegradability and can effectively reduce environmental pollution. In addition, the emission of harmful substances is reduced during the production process, which meets the requirements of sustainable development.
[0033] (4) During the production process, the present invention can flexibly control the performance of the adhesive by adjusting the degree of crosslinking and the ratio of ingredients to meet the needs of different application scenarios, thereby improving the market adaptability of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 The bonding strength result diagram of the plywood prepared in the embodiments of the present invention and the comparative examples;
[0036] Figure 2 The graph is a test result of wood breakage rate of plywood prepared in the embodiment of the present invention and the comparative example;
[0037] Figure 3 a is a graph showing the residual rate of adhesives in the embodiments of the present invention and the comparative examples;
[0038] Figure 3 b is a graph showing the moisture absorption rate of the adhesives of the embodiments of the present invention and the comparative examples;
[0039] Figure 4 The figure is a comparison chart of the mildew resistance of the adhesives of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0040] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0041] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0042] The percentage sign "%" involved in the present invention, unless otherwise specified, refers to mass percentage; however, the percentage of a solution, unless otherwise specified, refers to the number of grams of solute contained in 100 ml of the solution; the percentage between liquids refers to the volume ratio at 20°C.
[0043] The defatted soy flour (SP, protein content 50%) involved in the embodiment was provided by Shandong Linyi Shansong Biological Products Co., Ltd.; the poplar veneer (400×400×1.5mm) with a moisture content of 8% was provided by Allianz Wood Composite Materials Co., Ltd. (China); glacial acetic acid with a concentration of 99.5% was purchased from Shanghai McLean Biochemical Technology Co., Ltd.; chitosan (CS) with a deacetylation degree of 90% was purchased from Shanghai Yuanye Biotechnology Co., Ltd., and polyethyleneimine (PEI) with a molecular weight of 600 and a purity of 99% was provided by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0044] The preparation method of the triglycidylamine involved comprises the following steps:
[0045] Epichlorohydrin and ammonia water were added to the reactor in a mass ratio of 5:1 and stirred. Then, 0.5wt% of ammonium tricarboxylate was added as a catalyst, reacted at 23°C for 48h, and then heated to 40°C for 3h. Ammonium hydroxide and residual epichlorohydrin were removed by vacuum distillation to obtain 3-chloro-2-hydroxypropylamine. Then, 3-chloro-2-hydroxypropylamine was cooled to 20°C, excess 50% sodium hydroxide solution was added to seal the epoxy ring for 2h, the sodium chloride precipitate was filtered, and the light yellow viscous liquid TGA was obtained by vacuum distillation.
[0046] The preparation method of the chitosan@polyethyleneimine material involved comprises the following steps:
[0047] Take 4g of glacial acetic acid and dissolve it in 96ml of deionized water to make a 4% concentration solution, add 5g of chitosan (CS), stir at room temperature to dissolve the chitosan, and set the speed to 400r / min; add 2.5g of polyethyleneimine (PEI) solution to the flask, stir at room temperature to mix the polyethyleneimine evenly; put the mixture into a 60℃ constant temperature water bath and heat and stir for 6h to remove 75% of the water to obtain a CS@PEI modifier.
[0048] Example 1
[0049] This embodiment provides a soybean protein adhesive, comprising the following components in parts by weight:
[0050]
[0051] This embodiment also provides a method for preparing the above-mentioned soy protein-based adhesive, which specifically comprises the following steps:
[0052] (1) adding defatted soybean powder to deionized water, stirring at room temperature at an initial stirring speed of 200 r / min, then gradually increasing the stirring speed to 600 r / min for 20 min to obtain a homogeneous soybean protein adhesive system;
[0053] (2) Add triglycidylamine and chitosan@polyethyleneimine to the soy protein adhesive system, and mechanically stir for 15 min at 25° C. at a stirring speed of 600 r / min to obtain the adhesive.
[0054] Example 2
[0055] This embodiment provides a soy protein-based adhesive, comprising the following components in parts by weight:
[0056]
[0057] The preparation method of the soy protein-based adhesive provided in this embodiment is the same as that in Example 1.
[0058] Example 3
[0059] This embodiment provides a soy protein-based adhesive, comprising the following components in parts by weight:
[0060]
[0061]
[0062] The preparation method of the soy protein-based adhesive provided in this embodiment is the same as that in Example 1.
[0063] Example 4
[0064] This embodiment provides a soy protein-based adhesive, comprising the following components in parts by weight:
[0065]
[0066] The preparation method of the soy protein-based adhesive provided in this embodiment is the same as that in Example 1.
[0067] Comparative Example 1
[0068] This comparative example provides a soybean protein-based adhesive, which is different from Example 1 in that it does not contain triglycidylamine and chitosan@polyethyleneimine.
[0069] Comparative Example 2
[0070] This comparative example provides a soybean protein-based adhesive, which is different from Example 1 only in that it does not contain chitosan@polyethyleneimine.
[0071] Comparative Example 3
[0072] This comparative example provides a soybean protein-based adhesive, which is different from Example 1 only in that it does not contain triglycidylamine and chitosan@polyethyleneimine, and 6g of 5wt% CS is added.
[0073] Comparative Example 4
[0074] This comparative example provides a soybean protein-based adhesive, which is different from Example 1 only in that it does not contain triglycidylamine.
[0075] Example 5
[0076] Plywood was prepared using the soybean protein adhesives of Examples 1 to 4 and Comparative Examples 1 to 4, and the properties of each plywood were tested, as follows:
[0077] Plywood preparation process: According to the principle of single-sided gluing, the amount of glue applied was controlled by an electronic scale. The adhesives of Examples 1 to 4 and Comparative Examples 1 to 3 were coated at 200 g / m 2 The amount of glue was evenly coated on the poplar veneer. According to the principle of vertical arrangement of interlayer texture, three poplar veneers were stacked and combined, placed on the hot pressing bottom plate, and hot pressed using a flat plate vulcanizer (XLB-D500*500*1, Zhejiang, China). The hot pressing parameters were set as hot pressing pressure 1.0MPa; hot pressing temperature 120±3℃; hot pressing time 6min, and the sample was stored in a dry and ventilated environment for at least 24h to balance the moisture content.
[0078] Test the bonding strength, adhesive water resistance and mildew resistance of plywood.
[0079] Test Example 1 Bonding Strength
[0080] The plywood prepared with the soy protein adhesive of Examples 1 to 4 and Comparative Examples 1 to 4 was cut into 12 specimens using a circular saw according to the national standard GB / T17657-2022. The specimen size was 100×25mm, and the bonding area was controlled at 25×25mm. The plywood specimen size and its tensile loading schematic diagram are shown in the figure. The bonding strength test was carried out using a general electronic universal testing machine (CMT6104, Meters Industrial Systems, Minnesota, USA), and the shear rate was set to 10mm / min. Before the wet bonding strength was measured, the specimen was soaked in 63°C water for 3h, and then cooled at 25°C for 10min. The average shear strength of each group of specimens was calculated as the bonding strength. The bonding strength is calculated according to formula (1). According to national standards, the wet bonding strength of Class II plywood (indoor plywood) should be greater than 0.7MPa.
[0081]
[0082] After the sample test is completed, use a magnifying glass to observe the shear fracture surface, observe its surface damage under natural light, and calculate the wood breakage rate.
[0083] The results are as follows Figure 1As shown in the figure, the dry bonding strength of the plywood made with 1-SPI adhesive is 1.63MPa, and the wet bonding strength is 0.59MPa, which does not meet the national standard of Class II plywood greater than 0.7MPa. This is because there are more active groups in the soy protein adhesive, the hydrophobic groups in the three-dimensional structure of the molecule are located inside, and the hydrophilic groups are located outside, resulting in poor water resistance of the adhesive and failure to meet the strength requirements in a humid environment. Compared with SPI adhesive, after the addition of TGA, the dry / wet shear strength of SPI / TGA adhesive increased to 0.96MPa and 1.27MPa, respectively. This is attributed to the cross-linking reaction between the epoxy groups in TGA and the active groups in soy protein, forming a stable cross-linking network, which improves the bonding strength and water resistance of the adhesive. Compared with SPI adhesive, the dry and wet shear strengths of SPI / CS@PEI-4 / TGA increased by 106.8% and 17.8%, respectively, reaching 1.22MPa and 1.92MPa. This is because on the basis of the cross-linked network structure, TGA and CS@PEI undergo cross-linking reaction and hydrogen bond interaction to form a tighter network structure, thereby further improving the bonding performance of the plywood.
[0084] The wood breakage rate of the samples after mechanical testing was determined according to the national standard LY / T2720-2016. The wood breakage rate can, to a certain extent, indicate that the mechanical properties of the adhesive have been improved. A higher wood breakage rate means that the bonding strength of the adhesive itself is higher than the tensile strength that the wood can withstand. Figure 2 The test results show that the wood breakage rate of plywood using 1-SPI adhesive is low, only 14%, and the unmodified adhesive shows low cohesive strength, resulting in poor bonding performance. This phenomenon is mainly due to the physical entanglement between soybean protein molecules, which causes hydrogen bonds to break easily. The wood breakage rate of the adhesive test sample introduced with CS@PEI reached 68%, which indicates that the cohesion of the modified adhesive has increased and the bonding performance has improved. These data are consistent with the results of the moisture resistance test, indicating the good mechanical properties and water resistance of the CS@PEI modified adhesive.
[0085] Test Example 2 Water resistance
[0086] The adhesive samples of Examples 1-4 and Comparative Examples 1-3 were dried in a 120±3°C forced air oven to a constant weight, ground into 200 mesh powder, weighed to obtain a mass M, and the powder was wrapped with filter paper. The wrapped sample powder was immersed in deionized water at 63°C for 6 hours, and then placed in a 120°C oven to dryness. The mass m of the powder after immersion was weighed, and the residual rate was calculated using formula (2). Each sample was tested 3 times and the average value was taken.
[0087]
[0088] Residual rate and moisture absorption rate tests are important indicators for evaluating the water resistance of materials. Figure 3 As shown in a. The residual rate of 1-SPI is 50.5%. After the introduction of TGA cross-linking agent, the residual rate increased to 51.4%. This is because a network cross-linking structure is formed between TGA and soybean protein molecules, which effectively prevents the entry of moisture. After adding CS@PEI modifier, the residual rate of the adhesive is further increased to 64.6%, which is 27.92% higher than that of pure SPI adhesive. This is because the intermolecular bonding between CS@PEI and TGA forms a denser network structure with soybean protein molecules. Figure 3 b It can be seen that the moisture absorption rate of 1-SPI adhesive is 7.91%. This is because the soybean protein molecules contain a large number of hydrophilic groups. After adding CS@PEI modifier and TGA, the moisture absorption rate dropped to 6.94%, which was 12.26% lower than that of pure SPI adhesive. This is because the hydrophilic groups in soybean protein are consumed by the cross-linking reaction, and the physical strengthening effect of CS, etc., which improves the water resistance of the adhesive and effectively resists the invasion of water molecules.
[0089] Test Example 3 Anti-mildew performance
[0090] About 10 g of the adhesive samples of Examples 1-4 and Comparative Examples 1-3 were taken out and evenly spread on a glass culture dish with a diameter of 60 mm, and stored in a constant temperature and humidity chamber at 40° C. and 80% relative humidity to allow the soy protein adhesive to mold naturally. The mold conditions in the adhesive samples were regularly observed and recorded.
[0091] like Figure 4 As shown in the figure, pure soy protein adhesive quickly molds within 2 days, and bacteria multiply rapidly within 7 days, accompanied by the emission of odor. The production of mold will destroy the structure between soy protein molecules, and reduce the initial viscosity of the adhesive by producing hydrogen sulfide and carbon dioxide gas, which also makes the storage of the adhesive more difficult. Therefore, improving the mildew resistance of the adhesive is crucial to the storage and utilization of the adhesive. Figure 4 It can be observed that after the introduction of CS solution, the adhesive began to mildew slightly on the 5th day, and large patches of mildew began to appear after the 15th day, which was better than that of pure soy protein adhesive, but the improvement of mildew resistance was not high. It is speculated that it may be because the high acetic acid content denatured the soy protein and promoted the growth of mold. After the introduction of CS@PEI modifier and TGA crosslinker, it can be observed that the adhesive did not mildew within 30 days, which shows that the mildew resistance of the adhesive has been greatly improved.
[0092] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A tough and mildew-proof formaldehyde-free soybean protein adhesive, characterized in that: The invention comprises the following components in parts by weight: 100 parts of a main agent, 2-4 parts of a cross-linking agent, and 2-8 parts of a modifier, wherein the main agent is a defatted soybean powder solution, the cross-linking agent is one of bisphenol A epoxy resin, epoxy glycidyl ether, and triglycidyl amine, and the modifier is chitosan@polyethyleneimine.
2. The tough and mildew-proof formaldehyde-free soybean protein adhesive according to claim 1, characterized in that: The concentration of the defatted soy flour solution is 20-30%.
3. The tough and mildew-proof formaldehyde-free soybean protein adhesive according to claim 2, characterized in that: The preparation method of chitosan@polyethyleneimine comprises: adding 2-10 parts of chitosan to 80-100 parts of 2-10% concentration glacial acetic acid, mixing and dissolving, adding 2-5 parts of polyethyleneimine, mixing and heating, evaporating and removing 60%-80% of water, to obtain CS@PEI modifier.
4. The tough and mildew-proof formaldehyde-free soybean protein adhesive according to claim 3, characterized in that: The preparation method of chitosan@polyethyleneimine comprises: adding 80-100 parts of 4-6% concentration glacial acetic acid to 5-10 parts of chitosan to mix and dissolve, adding 2.5-5 parts of polyethyleneimine to mix, heating and evaporating to remove 75% of water to obtain CS@PEI modifier.
5. A tough and mildew-proof formaldehyde-free soybean protein adhesive according to claim 1, 2 or 4, characterized in that: The weight proportion of chitosan@polyethyleneimine is 4-6 parts.
6. The tough and mildew-proof formaldehyde-free soybean protein adhesive according to claim 1, characterized in that: The preparation method of triglycidylamine comprises: adding epichlorohydrin and ammonia water in a mass ratio of 5:1 into a reaction kettle and stirring, reacting under the action of a catalyst at 20-25° C. for 45-50 hours, and then at 30-40° C. for 2-4 hours, wherein the catalyst is 0.5wt% of ammonium tricarboxylate; The epichlorohydrin and ammonium hydroxide are removed by distillation to obtain a colorless slurry; an excess of sodium hydroxide solution is added to the colorless slurry, reacted at 18-22° C. for 1.5-3 hours, the sodium chloride precipitate is filtered, and a light yellow viscous liquid is obtained by vacuum distillation.
7. The tough and mildew-proof formaldehyde-free soybean protein adhesive according to claim 1, characterized in that: The defatted soy flour solution comprises defatted soy flour and a dispersion medium, wherein the dispersion medium is selected from one or more of tap water, softened water and deionized water.
8. The method for preparing the tough and mildew-proof formaldehyde-free soybean protein adhesive according to any one of claims 1 to 7, characterized in that: The steps include: The defatted soybean powder solution is stirred evenly, and a cross-linking agent selected from the group consisting of bisphenol A epoxy resin, epoxy glycidyl ether, and triglycidyl amine and chitosan@polyethyleneimine are sequentially added and stirred evenly to obtain a soybean protein adhesive.
9. The preparation method according to claim 8, characterized in that: The stirring is performed at 500-1000 rpm for 10-20 min.
10. A plywood prepared by bonding a board with the soybean protein adhesive according to any one of claims 1 to 7.
Citation Information
Cited By
Solid wood multi-layer waterproof moisture-proof formaldehyde-free environment-friendly marine furniture board and preparation process thereof
CN121083750A